Assessment of Bacterial Contaminants Associated with Hygiene Behaviour in Thai Tea Sold on the Roadside Around Educational Area, Lampung, Indonesia - Muhammad Asril; Ika Agus Rini; Rismawati Rismawati; Eka Fitriani Yuspiah; Muhammad Isa Ananta; Tarra Ivanka; Revi Agustin; Azisa Nabila Putri (JURNAL KESEHATAN LINGKUNGAN, 2023)
Introduction: Thai tea is one of the aromatic drinks widely sold around the Institut Teknologi Sumatera (ITERA), Lampung, Indonesia. Bacteria often contaminate this drink due to unhygienic handling. The number and types of contaminating bacteria have yet to be widely reported, especially in Lampung province. This study aimed to detect various bacterial contaminants in Thai tea beverages sold on the road in the ITERA region and their relationship with the hygiene behavior of Thai tea sellers. Methods: The sampling technique used in this study involved accidental sampling by detecting microbes using the most probable number method and the specific medium. The number and types of bacteria were analyzed for diversity and correlated with the behavior of Thai tea sellers. Results and Discussion: Of the 50 Thai tea samples, coliform bacteria, and Pseudomonas sp. in all samples (100%), Aeromonas sp. (36%), Shigella sp. (68%), Escherichia coli (76%), and Salmonella sp. (8%). The highest concentration of pollution occurred in Sukarame District (SK). SK10 had the highest number of contaminants, namely, Pseudomonas sp. (2.96x103±165 CFU ml-1), E. coli (7.2x103±190 CFU ml-1), Shigella sp. (3.35x103±350 CFU ml-1) and Salmonella sp. (9.65x103±50 CFU ml-1). The poor quality of Thai tea is caused by unhygienic tea raw materials and the habits of the seller, who does not perform hygienic tasks during the preparation and use of Thai tea. Conclusion: All samples did not meet the requirements for the presence of bacteria in drinking water, based on regulation No.492/MENKES/Per/IV/2010 and World Health Organization.